Analisis Tindak Tutur Direktif dalam Film Pendek Unggah-Ungguh - Lavania Indira Aruni; Kenfitria Diah Wijayanti; Rahmat Rahmat (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2024)
Directive speech acts are one of the parts studied in pragmatics which discusses how an utterance gives influence to others. Based on that, this research aims to explain the form and function of directive speech acts in Unggah-Ungguh short movie. The method used in this research is descriptive qualitative with pragmatic approach. The data of this research are phrases, and sentences in the short movie Unggah-Ungguh. The data were collected using document analysis technique. The sequence of this research is preparation, data collection, and compilation. This research found the use of six types of directive speech acts, namely 1) Requestives with the function of begging, asking, praying, inviting. 2) Questions with the function of asking. 3) Requirements with the functions of ordering, directing, commanding, and expecting. 4) Prohibitives with the function of prohibiting. 5) Permission with the functions of allowing, permitting, and approving. 6) Advice with the functions of advising, admonishing, and proposing.